1998
DOI: 10.3168/jds.s0022-0302(98)75827-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Parameters for 305-Day Yield, Fertility, and Survival in Holsteins

Abstract: A data file containing 122,715 lactation records of Holstein cows distributed across 11,374 herd-year-season groups was analyzed to obtain (co)variance estimates for yield, fertility and cow survival. Milk, fat, and protein yields were adjusted to 305 d. Days open was truncated to 305 d, and the number of services was truncated to 9. Survival of a cow during a full lactation (305 d) was recorded as 0 (died) or 1 (alive). Variance components for the six traits were estimated using a multiple-trait animal model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
135
5
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 61 publications
45
135
5
3
Order By: Relevance
“…As concluded by Royal et al (2002), although genetic correlations between milk production and fertility traits are unfavourable, they are not unity; it is not inevitable that fertility will decline as genetic merit for milk yield increases. Good management can foster high fertility and high yield in cows, but it will become increasingly difficult in the long term to maintain the current standards if fertility is not included in the breeding objective, as supported by findings of Dematawewa and Berger (1998).…”
Section: Genetic Correlations Between Longevity and The First Lactatimentioning
confidence: 91%
See 2 more Smart Citations
“…As concluded by Royal et al (2002), although genetic correlations between milk production and fertility traits are unfavourable, they are not unity; it is not inevitable that fertility will decline as genetic merit for milk yield increases. Good management can foster high fertility and high yield in cows, but it will become increasingly difficult in the long term to maintain the current standards if fertility is not included in the breeding objective, as supported by findings of Dematawewa and Berger (1998).…”
Section: Genetic Correlations Between Longevity and The First Lactatimentioning
confidence: 91%
“…This indicates that genetically reduced functional longevity is associated with increased genetic potential for fat and protein production. Dematawewa and Berger (1998) reported genetic correlations of longevity with MY1, FY1, and PY1 in the first lactation of 0.16, 0.20, -0.13, respectively. In contrast, Roxström and Stranberg (2002) reported a positive correlation between functional longevity and PY1 of 0.07, smaller than found in our study.…”
Section: Genetic Correlations Between Longevity and The First Lactatimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as discussed in more detail by Veerkamp et al (2008), there is † E-mail: mathijs.vanpelt@wur.nl clear evidence that genetic selection solely for milk yield has negative consequences for health and fertility, but it is not the absolute milk yield that apparently created the problems (Weigel, 2006;Windig et al, 2006). Also, studies on the trend in longevity over the past decades vary from the opinion that the effect of larger farms and (selection for) higher milk production have decreased the survival rate of dairy cows (Oltenacu and Broom, 2010;Froidmont et al, 2013), to the opinion that improved management and multi-trait genetic selection have had a positive impact on the survival of dairy cows (Dematawewa and Berger, 1998;Dechow and Goodling, 2008;Miglior et al, 2012). But, apart from the conflicting literature, there is little insight into how longevity has changed over the past decades, and the most important factors that play a role in the culling decisions of dairy farmers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was only the potential to produce milk that was included in this study. Many studies have found the genetic correlation between production and reproduction (Dematawewa and Berger, 1998;Veerkamp et al, 2001;Konig et al, 2008) and between production and health (Windig et al, 2006;Appuhamy et al, 2009) to be antagonistic. Conception rates and disease risks were kept constant over time in our simulation study.…”
Section: Discussionmentioning
confidence: 99%